Pengaruh Cash holding dan Financial leverage terhadap Income smoothing pada Perusahaan Sektor Makanan dan Minuman di Bursa Efek Indonesia Periode Pascapandemi COVID-19 - Muhammad Akbar Widya Putra; Oryza Tannar (Politeknik Ganesha Medan, 2026)
The post-pandemic economic recovery period of 2022–2024 has heightened uncertainties in corporate earnings stability, particularly within Indonesia's food and beverage sector. This study examines the effect of cash holding and financial leverage on income smoothing practices among food and beverage companies listed on the Indonesia Stock Exchange during that period. Grounded in agency theory and signaling theory, this research argues that both variables may create incentives for management to engage in earnings-smoothing behavior. A quantitative approach was employed using secondary data from annual audited financial reports. Purposive sampling yielded 47 companies, resulting in 141 firm-year observations over three years. Income smoothing was measured using the Eckel Index, cash holding was proxied by the ratio of cash and cash equivalents to total assets, and financial leverage was measured by the ratio of total debt to total assets. Binary logistic regression was applied using IBM SPSS 27. Results of the simultaneous test indicate that cash holding and financial leverage jointly influence income smoothing (sig. 0.049). Partially, cash holding has a significant negative effect on income smoothing (sig. 0.024), suggesting that higher cash reserves reduce the likelihood of earnings-smoothing practices. Financial leverage, however, shows no significant effect (sig. 0.142), indicating that debt pressure alone does not drive income smoothing in this sector during the post-pandemic recovery. These findings underscore the importance of strengthening corporate governance and transparency to safeguard the credibility of financial reporting.